AVALIAÇÃO DO USO DE RECURSOS HÍDRICOS EM REFINARIAS DE PETRÓLEO: UM ESTUDO DE CASO NA PETROBRAS - Collares, Stonesmogene (2004)
The rational use of water resources is certainly the more suitable way to prevent the gradual increase of world-wide water scarcity. This thesis is based on water and wastewater treatment plants of a Brazilian oil refinery. Using a base mass balance, opportunity studies are conducted in the process and unit operations with the aim of reducing the consumption of the water and the wastewater generation. Economical and technical analysis are used to choose the best option, using conventional and membrane technologies. The economic evaluation is conducted by using an available compilation of real data from the literature about American industries and membrane technology suppliers in Brazil.